Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1073/pnas.85.17.6399
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of embryonic genes in plants

Abstract: Somatic embryogenesis from cultured carrot cells progresses through successive morphogenetic stages termed globular, heart, and torpedo. To understand the molecular mechanisms underlying plant embryogenesis, we isolated two genes differentially expressed during embryo development. The expression of these two genes is associated with heart-stage embryogenesis. By altering the culture conditions and examining their expressions in a developmental variant cell line, we found that these genes were controlled by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The transcription of DC 59 is under strict developmental control, and both mRNA and protein are detected only in embryonic tissues (Borkird et al, 1988). Structural analysis showed that the gene was composed of a single exon resulting in an mRNA and a polypeptide with sizes that are in good correlation with previously published results (Choi et al, 1987).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The transcription of DC 59 is under strict developmental control, and both mRNA and protein are detected only in embryonic tissues (Borkird et al, 1988). Structural analysis showed that the gene was composed of a single exon resulting in an mRNA and a polypeptide with sizes that are in good correlation with previously published results (Choi et al, 1987).…”
Section: Discussionsupporting
confidence: 74%
“…However, the following three results suggest that they may play a role in the coordination of DC 59 gene expression: (1) The level of the C1 complex was correlated with the accumulation of DC 59 mRNA in callus and in embryos. DC 59 is expressed, although at Tower levels, in callus (Borkird et al, 1988). (2) Three of the four complexes could be detected only in embryos where the gene is highly active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some ABA-inducible LEA genes are inducible only in cells formed in the seed [ 14,32], while others appear to lack seed specificity [30,38]. Carrot LEA genes that encode hydrophilic proteins, such as DC8, are expressed in carrot zygotic embryo and endosperm tissues, in somatic embryos, and in callus [2,4,9,46]. The ABA treatment causes large increases in levels of mRNA and protein in cultured carrot cells, but ABA cannot induce DC8 expression in mature leaf or root tissues [14,18].…”
Section: Introductionmentioning
confidence: 99%